PEMBUATAN LEMAK KAKAO RENDAH KALORI DENGAN MINYAK KELAPA (COCONUT OIL)) MELALUI REAKSI INTERESTERIFIKASI - Lelya Hilda (JURNAL KIMIA MULAWARMAN, 2010)
Cacao fat has long chain fatty acids was high mainly palmitic and stearic can be improved their character by adding of palm oil to obtain cocoa fat was low calories. The addition of coconut oil can be done only up to 20%, which is the ratio (90:10) and (80:20) cocoa fat and coconut oil with solid fat content of 5:53 and 4:58 with a melting point 33.6 ° C and 32.8oC (32oC-35oC melting point cacao fat). The process was be done by interesterification reaction produces cocoa fat that free of trans fatty acids .Keywords: long chain fatty acaid, low calory, solid fat content, melting point